Faktor-faktor yang mempengaruhi penggunaan aplikasi online pada pelaku usaha mikro kecil dan menengah di Kota Jambi - Umiyati, Etik; Achmad, Erni (Jurnal Paradigma Ekonomika, 2021)
Digital developments make micro, small and medium enterprises must adjust to technological advances. the adoption of digital economic use of MSME actors is still relatively low. This is caused by several factors. The purpose of this study is to analyze the factors that influence the use of digital economy in SMEs in the City of Jambi. This study uses primary data with a purposive random sampling technique. The number of samples is 105 respondents. The analytical tool used is binary logit regression. Dependent variables are business actors who use digital (score = 1) and those who do not use digital (score = 0). The independent variable is household characteristics and business characteristics. From the results of the study obtained factors that influence MSMEs in using the digital economy are business type variables, information technology training, partnerships, age, education level and internet network. Â